Teaching and learning of tertiary skills via english language programs: the perceptions of tertiary ESL lecturers - Mohd Sharif, Nurhidayah (2015)
The embedment of tertiary skills through English Language Programs (ELPs) is believed to equip university students with a set of skills. Tertiary skills are a combination of generic skills, language skills and academic literacies which consist of (1) Communicative Skills, (2) Critical Thinking and Problem Solving Skills, (3) Team Working Skills, (4) Information Management and Life-long Learning Slulls, (5) Entrepreneurship Skills, (6) Leadership Skills and Proactiveness and (7) Ethics and Integrity. However, the way ELPs is designed at university somehow restricts the implementation of such skills to be effective. For that reason, this study aims to investigate English lecturers' perceptions on the teaching and learning of tertiary skills through ELPs at one university in Malaysia. In order to gain in-depth data, semistructured interviews were conducted with eight English lecturers and were later descriptively analyzed. The findings suggest that it is impossible to integrate all skills in one ELP as the nature of each ELP is to develop certain skills only. In terms of pedagogical and methodological aspects, tertiary skills are implemented from the constructivist point of view. According to the lecturers, in general, the students demonstrated a modest level of tertiary skills acquisition. This study concludes that ELPs can be the right platform to offer students with not only knowledge related to language but also various other skills required at tertiary level. This study also offers insights into the effective syllabus design for tertiary ESL programs.